Effectiveness of Modular Approach in Teaching Primary Grades Amidst Pandemic Education - Barola, Rene Cabrea (Jurnal Pendidikan Progresif, 2023)
Effectiveness of Modular Approach in Teaching Primary Grades Amidst  Pandemic Education. Objectives: This study determined the effectiveness of modular approach in teaching primary grades amidst pandemic education. Specifically, this investigated the profile of the primary grade teachers, level of effectiveness of modular approach in teaching primary grades and the suggestions to enhance the implementation of printed modular learning amidst pandemic education. Methods: Descriptive survey research design was used which described data gathered  from 96 purposively selected respondents .Survey using questionnaire with 5-point Likert Scale was utilized by the study. Data were tabulated and appropriately treated using frequency count, percentage and weighted mean. These provided the most fit way of analysis and interpretation of the research data. Findings: An over-all weighted mean of 3.53 for the level of effectiveness on modular approach in teaching primary grades amidst pandemic education was computed.Conclusion: The primary grades teachers were dominated by female teachers. A high effectiveness on modular approach in teaching Grades 1,2 and 3 learners was achieved. There were also various suggestions to enhance the implementation of printed modular learning amidst pandemic education. Keywords: modular approach, modules, teaching, primary grades, pandemic education.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202348